2016
DOI: 10.1021/jacs.6b00111
|View full text |Cite
|
Sign up to set email alerts
|

A Multivalent Marine Lectin from Crenomytilus grayanus Possesses Anti-cancer Activity through Recognizing Globotriose Gb3

Abstract: In this study, we report the structure and function of a lectin from the sea mollusk Crenomytilus grayanus collected from the sublittoral zone of Peter the Great Bay of the Sea of Japan. The crystal structure of C. grayanus lectin (CGL) was solved to a resolution of 1.08 Å, revealing a β-trefoil fold that dimerizes into a dumbbell-shaped quaternary structure. Analysis of the crystal CGL structures bound to galactose, galactosamine, and globotriose Gb3 indicated that each CGL can bind three ligands through a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…The Mitsuba-1 model, like MytiLec, shows no evidence of a significant role for water at any of the three sites in the asymmetric unit 9 . Each sugar ligand is well-ordered in the electron density map determined for Mitsuba-1 (Supplementary Figure 5), suggesting tight binding, but from earlier work with MytiLec 9 and CGL 28, 30 it is known that each binding site alone has rather weak affinity, and the avidity of the protein for cell surfaces displaying suitable sugar ligands arises from the multiplicity of sites. Using calorimetry, Mitsuba-1 was found to bind N-acetylgalactosamine with a K d of 0.33 mM (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The Mitsuba-1 model, like MytiLec, shows no evidence of a significant role for water at any of the three sites in the asymmetric unit 9 . Each sugar ligand is well-ordered in the electron density map determined for Mitsuba-1 (Supplementary Figure 5), suggesting tight binding, but from earlier work with MytiLec 9 and CGL 28, 30 it is known that each binding site alone has rather weak affinity, and the avidity of the protein for cell surfaces displaying suitable sugar ligands arises from the multiplicity of sites. Using calorimetry, Mitsuba-1 was found to bind N-acetylgalactosamine with a K d of 0.33 mM (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Unsurprisingly, the top hits are models of MytiLec 9 and CGL 27, 28 (for example PDB models 3WMV and 5DUY), sharing a Z-score of 27.2, and a number of β -trefoil proteins are detected. Less expected was that the Threefoil model, with a Z-score of 23.5, ranked slightly behind Ct1, an exo-beta-1,3-galactanase from Clostridium thermocellum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Copurification of endogenous carbohydrates with recombinant proteins has been uncommonly encountered in previous studies (39) because of generally relatively low binding affinity (∼millimolar) between noncognate glycans and GBPs (40). Nonetheless, our studies strongly suggest Y3 to be a GBP.…”
Section: Resultsmentioning
confidence: 51%
“…We used cDNA sequencing to determine the amino acid sequence of CGL and found that CGL exhibited antibacterial and antifungal activities in the shellfish by being involved in the recognition and clearance of bacterial pathogens 18, 19 . Recently, we determined the crystal structure of CGL, which revealed the presence of a β-trefoil fold that dimerizes into a dumbbell-shaped quaternary structure in the protein 20 .…”
Section: Introductionmentioning
confidence: 99%